Purifying or polluting? Tracing membrane-based microplastics release for long-term drinking water safety - Shunyao Yu; Siming Xie; Yaya Zhu; Wei Wang; Zhitong Liu; Xian Bao; Jun Ma (Water Research, 2026)

Ultrasonic-enzymatic synergistic extraction of Ophiopogon japonicus polysaccharides: Structural characterization, in vitro hypoglycemic activity, and regulatory mechanism on human gut microbiota - Junlin Wu; Meng Wang; Yutong Liao; Sijie Huang; Xincheng Ye; Fengchuan Ma; Siming Zhu; Yunping Peng; Dan Xu (Food Bioscience, 2026)

Corrigendum to “Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region”. [Catena 260 (2025) 109423] - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

Effects of herbaceous plant roots on tensile strength of root-soil composite in loess hilly region - Sijing Zhang; Jianye Ma; Siming Liu; Longyu Zhang; Zhanbin Li; Fangtao She; Jiulong Ding; Peng Li; Chengcang Tian (CATENA, 2025)

The development of thickened fermented rice milk formulation for people with dysphagia: A view of multiple in vitro simulation methods - Zexue Lin; Lingling Ma; Bowen Li; Siming Zhao; Binjia Zhang (Food Research International, 2025)

Activation of the NLRP3-CASP-1 inflammasome is restrained by controlling autophagy during Glaesserella parasuis infection - Chaoxiong Yue; Jinquan Li; Siming Zhang; Ruyi Ma; Mingjiao Suo; Yiwen Chen; Hui Jin; Yan Zeng; Yushan Chen (Veterinary Microbiology, 2024)

Research progress on the adsorption of sulfocompounds in flue gas - Siming Guo; Qingjun Yu; Shunzheng Zhao; Xiaolong Tang; Ya Wang; Yiming Ma; Yuhan Long; Honghong Yi (Chemical Engineering Journal, 2023)

Kif15 deficiency contributes to depression-like behavior in mice - Junpei Wang; Qifeng Tu; Siming Zhang; Xiaomei He; Chao Ma; Xiaowei Qian; Ronghua Wu; Xinyu Shi; Zhangyi Yang; Yan Liu; Zhangji Dong; Mei Liu (Metabolic Brain Disease, 2023)

Degradation characteristics of intracellular and extracellular ARGs during aerobic composting of swine manure under enrofloxacin stress - Jiaojiao Xu; Jielan Huang; Longhai Chen; Majian Chen; Xin Wen; Pengfei Zhang; Siming Li; Baohua Ma; Yongde Zou; Yan Wang; Xindi Liao; Yinbao Wu (Chemical Engineering Journal, 2023)

Genetic perturbation of mitochondrial function reveals functional role for specific mitonuclear genes, metabolites, and pathways that regulate lifespan - Cheryl Zi Jin Phua; Xiaqing Zhao; Lesly Turcios-Hernandez; Morrigan McKernan; Morteza Abyadeh; Siming Ma; Daniel Promislow; Matt Kaeberlein; Alaattin Kaya (GeroScience, 2023)
Altered mitochondrial function is tightly linked to lifespan regulation, but underlying mechanisms remain unclear. Here, we report the chronological and replicative lifespan variation across 167 yeast knock-out strains, each lacking a single nuclear-coded mitochondrial gene, including 144 genes with human homologs, many associated with diseases. We dissected the signatures of observed lifespan differences by analyzing profiles of each strain’s proteome, lipidome, and metabolome under fermentative and respiratory culture conditions, which correspond to the metabolic states of replicative and chronologically aging cells, respectively. Examination of the relationships among extended longevity phenotypes, protein, and metabolite levels revealed that although many of these nuclear-encoded mitochondrial genes carry out different functions, their inhibition attenuates a common mechanism that controls cytosolic ribosomal protein abundance, actin dynamics, and proteasome function to regulate lifespan. The principles of lifespan control learned through this work may be applicable to the regulation of lifespan in more complex organisms, since many aspects of mitochondrial function are highly conserved among eukaryotes.

Understanding spatial-temporal travel demand of private and shared e-bikes as a feeder mode of metro stations - Siming Liu; Fan Zhang; Yanjie Ji; Xinwei Ma; Yong Liu; Shuo Li; Xizhen Zhou (Journal of Cleaner Production, 2023)

Photocatalytic removal of elemental mercury via Ce-doped TiO2 catalyst coupling with a novel optical fiber monolith reactor - Feng Xin; Siming Ma; Jianping Yang; Yongchun Zhao; Junying Zhang; Chuguang Zheng (Environmental Science and Pollution Research, 2020)

Emission controls of mercury and other trace elements during coal combustion in China: a review - Yongchun Zhao; Jianping Yang; Siming Ma; Shibo Zhang; Huan Liu; Bengen Gong; Junying Zhang; Chuguang Zheng (International Geology Review, 2018)

Dissimilar characteristics of umbilical cord mesenchymal stem cells from donors of different ages - Sha Huang; Changjiang Feng; Yan Wu; Siming Yang; Kui Ma; Xu Wu; Xiaobing Fu (Cell and Tissue Banking, 2013)